2006
DOI: 10.1117/1.2360525
|View full text |Cite
|
Sign up to set email alerts
|

Molecular contrast optical coherence tomography: a pump-probe scheme using indocyanine green as a contrast agent

Abstract: Abstract. The use of indocyanine green ͑ICG͒, a U.S. Food and Drug Administration approved dye, in a pump-probe scheme for molecular contrast optical coherence tomography ͑MCOCT͒ is proposed and demonstrated for the first time. In the proposed pump-probe scheme, an optical coherence tomography ͑OCT͒ scan of the sample containing ICG is first acquired. High fluence illumination ͑ϳ190 kJ/ cm 2 ͒ is then used to permanently photobleach the ICG molecules-resulting in a permanent alteration of the overall absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…On the ground state potential, molecules either relax back to the trans configuration or form a cis isomer [8,9]. In our previous study, we irradiated two near-infrared (NIR) ultrashort pulses on indocyanine green (ICG), a widely used and investigated dye [10][11][12][13][14][15][16][17], and measured transient absorption by photo-produced cis-isomers as a function of pump-pump interval, in other words two-pulse correlation (2PC) trace [7]. We found that the transient absorption shows clear dependence on pumppump interval and increases with decrease of the interval.…”
Section: Introductionmentioning
confidence: 99%
“…On the ground state potential, molecules either relax back to the trans configuration or form a cis isomer [8,9]. In our previous study, we irradiated two near-infrared (NIR) ultrashort pulses on indocyanine green (ICG), a widely used and investigated dye [10][11][12][13][14][15][16][17], and measured transient absorption by photo-produced cis-isomers as a function of pump-pump interval, in other words two-pulse correlation (2PC) trace [7]. We found that the transient absorption shows clear dependence on pumppump interval and increases with decrease of the interval.…”
Section: Introductionmentioning
confidence: 99%
“…This differed from previous methods that enhanced contrast by means of characteristic spectral OCT signal shift due to absorption effects from indocyanine green dye [5] or nanoparticles [6][7][8]. The reasoning was that absorption effects would be too small for small clusters of GNR in a sparse concentration of cells to produce useful contrast.…”
Section: Introductionmentioning
confidence: 57%
“…Polarization-sensitive OCT is used to measure phase retardation in birefringent tissue which has application in retinal imaging [110], burn-depth determination [111], atherosclerosis imaging [112], muscular dystrophy [113], and detection of basal cell carcinomas [114]. Pump-probe OCT [115,116] and nonlinear interferometric vibrational imaging [117] are also promising methods to sense endogenous biomolecules based on their nonlinear optical susceptibilities. Although these endogenous methods are attractive as they do not require the addition of exogenous agents for contrast, they may be limited in scope because many diagnostic markers do not exhibit a detectible optical signal.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…11 OCT images of tissue phantoms with varying concentrations of plasmon-resonant nanorods, as described in[115,119]. Left and right columns are the structural OCT and their associated spectroscopically contrasted nanorod OCT images, respectively.…”
mentioning
confidence: 99%